1992
DOI: 10.1007/bf02540939
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic transfer hydrogenation of soybean oil

Abstract: The catalytic transfer hydrogenation of soybean oil by various hydrogen donors and solvents with palladium-oncarbon catalyst was investigated in batch and continuous modes. The choice of reaction conditions, donor and catalyst allowed the manufacture of partially hydrogenated oils or semi-solid fats with controlled fatty acid contents, iodine value, melting point and solid content index. The level of "iso" forms of fatty acids was similar to, and average initial selectivity was higher than that obtained with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 16 publications
(18 reference statements)
1
30
0
Order By: Relevance
“…Moreover, no special reactors are required and the solvent is used as a hydrogen donor along with a selected catalyst. The CTH process using Pd/C catalyst and different hydrogen donor solvents have also been reported for soy [31], sunflower [32], and castor [16,33] oils.…”
Section: Hydrogenationmentioning
confidence: 99%
“…Moreover, no special reactors are required and the solvent is used as a hydrogen donor along with a selected catalyst. The CTH process using Pd/C catalyst and different hydrogen donor solvents have also been reported for soy [31], sunflower [32], and castor [16,33] oils.…”
Section: Hydrogenationmentioning
confidence: 99%
“…The dominant mechanism of hydrogenation in the present investigation involves the use of formic acid to transfer hydrogen to the canola oil (Scheme 1). Research (8) has shown that the formate ion can be used for hydrogenation of vegetable oils under the temperature conditions used in this study. One of the products of chemical reaction between the formate ion and vegetable oil in the presence of water is the bicarbonate anion.…”
Section: Resultsmentioning
confidence: 98%
“…DDAB was obtained from Fluka (St. Louis, MO), and sodium formate (99.8%) and formic acids (97%) were obtained from Alfa Essar (Ward Hill, MA). Both sodium formate and formic acid are approved food-grade materials that have been used in past research to hydrogenate edible oils (8,9). Formic acid is used as a preservative and flavor adjunct (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic transfer hydrogenation (CTH) is a common procedure in organic chemistry, although there are only a few examples of CTH being used for the hydrogenation of vegetable oils (11)(12)(13). The advantage of CTH, compared with classical heterogeneous systems, is its simplicity: It requires only moderate temperatures and pressures, with the hydrogen donor (usually formic acid or alcohols) being used as the solvent and nickel (Ni) or palladium (Pd) as the catalyst.…”
mentioning
confidence: 99%